Chemical reactivity theory (CRT) study of small drug-like biologically active molecules. Issue 3 (11th February 2021) - Srivastava, Ruby
Abstract: New biochemical screening and design based technology are used to identify the small molecules in targeting RNA. These approaches has develop potential drug like small molecule for RNA-targeted therapeutics. Chemical Reactivity Theory (CRT) is used to study these drug-like, biologically active small molecules that target RNA. Twenty two small molecules based on structure (1–6 ), information (7–9 ), fragment (10–19 ), small molecular microarrays (20 ), and use of phenotypic assays (21–22 ) are selected for the studies of several DFT-based global reactivity and local reactivity descriptors to provide complete explanation for the reactivity of these complexes by chemical reactivity method. Higher HOMO-LUMO gap indicated the structural stability for the studied complexes. The complexes reflect greater thermodynamic stability. Further the results predicted that high aromaticity and hardness are measures of high stability and low reactivity for the studied complexes. It was observed that a good, more reactive, nucleophile can be described by a lower value of μ, ω while a good electrophile can be described by a high value of μ, ω. TDDFT results predicted that few complexes can be used as fluorescent biomarkers as their emission wavelength lies in the visible region. Communicated by Ramaswamy H. Sarma